Aspects of pathomorphology and nomenclature in the modern classification of nonspecific osteomyelitis - Hryhorovskyi, Valeriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
On the basis of his own experience of scientific and clinical researches, analysis of experimental-morphological and clinical-bioptic materials the author deals with problems of terminology and morphological pathology, which are important for creating a modern multiple-aspect classification of inflammatory lesions of bones. The work is based on results of examination of more than 1,800 experimental and clinical cases of osteomyelitis. The researcher isolates key aspects in theoretical concepts of nonspecific osteomyelitis, namely: the origin of the inflammatory process in bone (aetiology and pathogenesis), which determines isolation of nosological units; stages and periods of osteomyelitis; spatial organization of the focus of a nonspecific lesion of bone; the kind of the exudative and/or productive inflammatory process in the capsule, its structure; peculiarities of the bone tissue lesion; information about complications and outcomes of osteomyelitis. The author believes that, besides solving diagnostic problems, results of scientific researches, based on analysis of morphological features of the focus, should form the foundation of a modern multiple-aspect clinical-morphological classification of nonspecific inflammatory lesions of bone, thereby creating a basis for further researches in osteomyelitis, an adequate assessment of efficacy of methods for its diagnosis and treatment.